Association of Glycemic Control with Diabetic Nephropathy among Patients with Type 2 Diabetes Mellitus in Pakistan (Journal of Fatima Jinnah Medical University, 2025)
Background: Diabetic nephropathy is a common microvascular complication of diabetes mellitus and is a cause of significant morbidity and mortality. This study explores the relationship of HbA1c with diabetic nephropathy in Pakistani population.Patients and methods: A cross-sectional study was conducted at the Internal Medicine Department of Shaikh Zayed Medical Complex (SZMC), Lahore, on patients with type 2 diabetes. Mean HbA1C levels were compared between patients with and without diabetic nephropathy by applying independent sample t-test, while suboptimal glycemic control was compared using chi-square test. Pearson’s correlation was applied to assess the correlation of urinary albumin levels with duration of diabetes and HbA1c levels.Results: A total of 80 patients with type 2 diabetes mellitus were included in the study. The mean age of all the participants was 47 + 10 years. Out of these cases, 56.3% were male and 43.8% were female. Suboptimal glycemic control was present in 72.5% cases and 47.5% were diagnosed with diabetic nephropathy. Higher mean HbA1c levels were observed in the patients with nephropathy as compared to those without nephropathy (10.1 + 1.1% vs 7.2 + 0.8%, p < 0.001). All diabetic nephropathy cases (100%) had suboptimal glycemic control as compared to 47.6% of the cases without nephropathy (p < 0.001). The 24-hours urinary proteins had a strong correlation with HbA1c levels (r = 0.771, p < 0.001) and a moderate correlation with duration of diabetes (r = 0.638, p
Keywords: Type 2 diabetes mellitus; diabetic nephropathy; diabetes complications; glycemic control; albuminuria